Empirical analysis of natural gas markets - David A. Anderson; Shigeyuki Hamori (MDPI, 2020)
Recent developments in the natural gas industry warrant new analysis of related issues. Environmental, social, and governance (ESG) investments have accelerated the shi􀀴 away from coal as the dominant source of electricity. Its low environmental impact, reduced volume, and broad availability make liquefied natural gas (LNG) a popular alternative, during this time of transition between traditional fuels and newer options. In the United States, the shale gas revolution has made natural gas a game changer. In this book, we focus on empirical analyses of the natural gas market and its growing relevance worldwide.
Keywords: 330; Erdgasmarkt; Branchenentwicklung; USA; Welt